2019
DOI: 10.4103/lungindia.lungindia_61_19
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of obesity hypoventilation syndrome among patients with sleep-disordered breathing in India

Abstract: Introduction:No study has been done in India to evaluate obesity hypoventilation syndrome (OHS) among patients with sleep-disordered breathing (SDB). The known predictors of OHS, i.e., body mass index (BMI) >35 kg/m2 and forced vital capacity (FVC) <3.5 L for men and <2.3 L for women from western countries, cannot be applied to Indian patients.Objectives:To find out the prevalence of OHS and to determine the predictors of OHS among Indian SDB patients.Materials and Methods:It was a retrospective observational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…A similar finding was observed in a study done by Schreiber et al 20 Higher age is one of the risk factors of OSA in the general population. 21 So, questionnaires like "STOPBang" which GOLD grade 2 GOLD grade 3 GOLD grade 4 COPD-OSA ( 14) COPD (23) p-value COPD-OSA (13) COPD (28) includes high age as risk factors are possibly unreliable screening tools for COPD-OSA overlap syndrome. The lower mean age of COPD-OSA overlap syndrome patients in our study can be explained by the fact that these patients present the syndrome at younger age owing to the severity of symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar finding was observed in a study done by Schreiber et al 20 Higher age is one of the risk factors of OSA in the general population. 21 So, questionnaires like "STOPBang" which GOLD grade 2 GOLD grade 3 GOLD grade 4 COPD-OSA ( 14) COPD (23) p-value COPD-OSA (13) COPD (28) includes high age as risk factors are possibly unreliable screening tools for COPD-OSA overlap syndrome. The lower mean age of COPD-OSA overlap syndrome patients in our study can be explained by the fact that these patients present the syndrome at younger age owing to the severity of symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the Asian patients with OSA had lower BMI and different cephalometric parameters. [26][27][28] Patients with OSA commonly have EDS. But EDS cannot be taken as a predictor of OSA in COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Japanese individuals with OHS tend to be younger than OSA patients [ 41 , 42 ], while in the Middle East, OHS patients appear to be older than OSA patients [ 43 , 44 ]. East Asian [ 45 ] and Indian [ 46 ] populations tend to develop OHS at lower BMIs than non-Asian populations. Reflecting upon these ethnic differences, S aeseow et al .…”
Section: Serum Bicarbonatementioning
confidence: 99%
“…Obesity and a family reduced response to hypercapnia are likely two distinct causes of respiratory failure in the child with obesityhypoventilation syndrome. Only a tiny number of obese patients experience the obesity-hypoventilation syndrome, which may be explained by the hereditary aspect [10][11][12]. Although the obesity-hypoventilation syndrome in children is uncommon, it can have catastrophic consequences and has a high death rate.…”
Section: Introductionmentioning
confidence: 99%

Overview on Pediatric Obesity Hypoventilation Syndrome

Fadl,
Mashael Abdulaziz Shahatah,
Atheer Yahya S Asiri
et al. 2023
SMHJ